2011
DOI: 10.1590/s1676-06032011000400014
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and density estimates of the anurofauna of a site within the northernmost large Atlantic Forest remnant (Parque Estadual do Desengano) in the state of Rio de Janeiro, Brazil

Abstract: We present data on species composition, relative abundance and estimated densities for leaf-litter anuran amphibians from an Atlantic Forest area within the Parque Estadual do Desengano, in the state of Rio de Janeiro, Brazil, based on results of a short-term survey carried out during the winter at altitudes of 1000-1500 m. Three sampling methods were used: plot sampling, visual encounter surveys (VES; performed during the day, at the twilight, and at night), and pitfall traps. We recorded 13 species, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The estimated overall density of the local leaf litter frog assemblage was high (18.1 ind/100 m 2 ) when compared to those found for most other sites sampled (also with large quadrats) within the Atlantic Forest in southeastern and southern Brazil (1.4-13.2 ind/100 m 2 ; Giaretta et al 1997, Rocha et al 2001, 2013, Almeida-Gomes et al 2008, Santos-Pereira et al 2011, Siqueira et al 2011a, Oliveira et al 2013. Exceptions are two localities in the municipality of Cachoeiras de Macacu, state of Rio de Janeiro, that yielded comparable (17.1 ind/100 m 2 ; Siqueira et al 2009) or higher estimates (24.6 ind/100 m 2 ; Siqueira et al 2014).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The estimated overall density of the local leaf litter frog assemblage was high (18.1 ind/100 m 2 ) when compared to those found for most other sites sampled (also with large quadrats) within the Atlantic Forest in southeastern and southern Brazil (1.4-13.2 ind/100 m 2 ; Giaretta et al 1997, Rocha et al 2001, 2013, Almeida-Gomes et al 2008, Santos-Pereira et al 2011, Siqueira et al 2011a, Oliveira et al 2013. Exceptions are two localities in the municipality of Cachoeiras de Macacu, state of Rio de Janeiro, that yielded comparable (17.1 ind/100 m 2 ; Siqueira et al 2009) or higher estimates (24.6 ind/100 m 2 ; Siqueira et al 2014).…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, this small direct-developing anuran numerically dominated the anuran assemblage at the studied site in the APA Serra da Mantiqueira (as also evidenced by the VES methodology). Several other plotsampling studies in Atlantic Forest areas have also evidenced a clear dominance of species with direct development of terrestrial eggs in the local leaf-litter frog assemblages (e.g., Giaretta et al 1997, Rocha et al 2001, 2013, Almeida-Gomes et al 2008, Siqueira et al 2009, 2011a, and this has also been observed in Amazonian (e.g., Rodriguez 1992, Gascon 1996 and Central American forest areas (e.g., Scott 1976, Toft 1981, Liebermann 1986, Fauth et al 1989, Hofer & Bersier 2001. Direct-developing anurans may be more widely distributed within the forest due to their independence of water bodies for reproduction (Haddad & Prado 2005), though other factors such as rates of dehydration/rehydration (Dabés et al 2012) and a generalist diet (Alves-dos- Santos et al 2021) may also play a role.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Thus, the state of Rio de Janeiro, in spite of its relatively small territorial extension, contains approximately 19% of the amphibian species known to occur in Brazil and nearly 40% of the Atlantic Forest amphibian species. Nevertheless, the list reported herein for Rio de Janeiro is likely still far from exhaustive, judging by the numerous recent reports of undescribed species from throughout the state, including members of genera such as Brachycephalus (Siqueira et al, 2011a(Siqueira et al, , b, 2013, Ischnocnema (Siqueira et al, 2011b;Gehara et al, 2013), Euparkerella (Fusinatto et al, 2013), Adenomera (Fouquet et al, 2014), Fritziana (Siqueira et al, 2011b;Castroviejo-Fisher et al, 2015), Aplastodiscus (Berneck et al, 2016), and Scinax (Bittencourt- . This indicates that the current amphibian richness recorded for the state is still an underestimate, and is likely to increase in the years to come following the intensification of taxonomic studies and of local herpetofaunal surveys.…”
Section: Conservation Remarksmentioning
confidence: 93%